Paradoksy w wyjaśnianiu świadomości - POCZOBUT, Robert (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
There is a widely held and deeply rooted conviction that consciousness is something mysterious and paradoxical. Yet despite this belief interdisciplinary research is conducted nowadays with the objective to explain the origin, structure and function of consciousness. Throughout the process, the following questions arise: Are mysterians right in claiming that consciousness will always remain outside the explanatory capabilities of science? Or should we rather put faith in the assertions of the scientists and philosophers who hold that the puzzle of consciousness will soon be solved and the paradoxes related to it rendered merely ostensible? In the present article, I scrutinize some theoretical diffi culties engendered by four different projects developed with the goal to explain consciousness. The fi rst one seeks neural correlates of consciousness, the second stresses the need to construct a causal explanation; the third postulates that onsciousness should be explained by means of the fundamental mental and physical laws, and the fourth refers to the mechanistic model of explanation accepted within neurocognitivism. Translated by Dorota Chabrajska